INGGRIS - Lingga Kusuma Wardani; Junan Hilmi Fawaid (Jurnal Ilmu Keperawatan Jiwa, 2022)
The role of parents in raising and nurturing a child is not an easy thing, it requires energy, cohesiveness and patience in guiding children according to the character, especially the child's discipline in learning. The purpose of to analyze the influence of parenting patterns on the psychosocial development the digital era in Bendorejo Village, Pogalan District, Trenggalek. The study was conducted with a obsrvasional analytic approach using questionnaire. Data were analyzed using logisti regression in the form of frequency distribution.The results showed that most of the respondents had a permissive parenting category as many as 31 respondents (57.4%). Most of the respondents experienced less psychosocial development as many as 30 respondents (56.6%). The results of research concluded there is an influence of parenting patterns on the psychosocial development of elementary school children aged 7-9 years in the digital era in Bendorejo Village, Pogalan, Trenggalek.